Effects of Surrounding Landscape Context on Threatened Wetland Bird Diversity at the Global Scale - Lihe Li; Yiwen Liu; Haokun Wang; Yemeng Zhu; Yuxiang Li; Chi Xu; Shuqing N. Teng (Diversity)
Wetland birds are undergoing severe population declines globally, primarily attributed to extensive wetland loss and degradation. The attributes of the landscape surrounding a focal locality, referred to as ‘landscape context’, have been shown to influence the diversity of wetland birds living in the given area. At a global scale, however, the landscape context effects on wetland birds have not been assessed. Here, we assessed the effect of landscape context on the richness of threatened bird species recorded in 334 inland Ramsar wetland sites across the globe. Generalized linear mixed models were used to quantify the relationship between the richness of these bird species and the landscape context of the Ramsar sites. Variation partitioning was used to quantify the independent explanatory power of landscape context for comparison between migratory and non-migratory species. The overall and independent explanatory power of landscape context for the global-scale richness pattern of threatened avifauna reached ca. 17% and 3%, respectively, with the scale of peak explanatory power being 5 times the area of a focal Ramsar site. The independent explanatory power of landscape context was significantly higher for migratory species (ca. 30%) than for non-migratory ones (ca. 3%). Among the landscape context metrics, wetland habitat loss and fragmentation were most strongly associated with the global-scale richness of threatened migrant species at Ramsar sites. Our results suggest that even at macroecological scales, landscape context contributes to shaping the richness pattern of threatened bird species, especially for migrants. These findings provide useful insight for managing landscapes surrounding Ramsar sites, in order to improve conservation effectiveness for wetland birds worldwide.